Towards real-world biomechanical detection of fatigue, energy, and injury in runners using wearable trunk accelerometry - Schütte, K. (Stellenbosch University, 2018)
Running continues to be an extremely popular form of exercise and sport. Unfortunately, many runners, both recreational and competitive, fail to meet their fitness and performance goals due to sustaining an overuse injury. Such overuse injuries can be due to numerous environmental factors and internal factors. Therefore, any approach to identifying and minimizing these risk factors in real-life running conditions will help runners to reach their training goals while also to regain running`s numerous health benefits. Running requires minimal equipment and can be performed on practically any terrain. Ideally, measurements of a runner`s mechanics should follow the runner through his or her typical training environment and be unrestricted to location. However, such measurements may require a totally different experimental approach compared to those traditionally performed in the laboratory (i.e. capture and analyse every stride of the runner outdoors rather than providing only a `snapshot` view). Over two decades ago it was acknowledged that obtaining objective data in real-life environments using wearable technology is of high priority with potential to advance running performance while also reducing injury risk. Even with recent and rapid technology advancements, there remains a paucity of literature linking the fields of wearable technology with running related performance and injury risk. Thus, the global objective of this thesis is to expand understanding with regards to detecting fatigue-, energy-, and injury-related dynamic instability and dynamic loading in runners using wearable trunk accelerometry (WTA), with transferability to `real-world` ecologically valid settings. In the first part of this thesis, we performed two indoor laboratory studies focusing firstly on the biomechanical, and secondly on the energetic aspects of running. Study I (chapter 2) biomechanically confirmed a fatigue-ability hypothesis, showing that runners incur a loss of stability from running-induced fatigue specific to laboratory-controlled treadmill running conditions at fixed speeds. Study II (chapter 3) physiologically confirmed a cost of instability hypothesis, revealing that certain aspects of dynamic stability are energetically advantageous to endurance running. In the second part of this thesis we performed two outdoor over-ground running experiments. Study III (chapter 4) experimentally showed that running on an irregular outdoor surface such as wood-chip trails disrupts aspects of stability specific to the mediolateral direction. Study IV (chapter 5) partially confirmed a fatigue-ability and injury hypothesis, showing that runners with history of medial tibial stress syndrome (MTSS) incur a loss of stability in the mediolateral direction from outdoor track-running at self-selected speeds. Finally, the general discussion (chapter 6) brings together findings with practical implications directed at runners, researchers, and practitioners. In addition, some preliminary data with regards to running stability before, during, and after an endurance training program are provided, with potential insights and future directions aimed at performance and injury detection. Overall, this doctoral thesis contributes to a better understanding of a runner`s dynamic stability and loading in relation to fatigue, energy and injury using wearable trunk accelerometry.